Pendampingan Pengelolaan Media Sosial melalui Feed Instagram sebagai Alat Promosi - Silfiani, Rohmatul Ula; Laeli, Ayu Halmi; Uriavita, Desta Eci; Khoiriyah, Lia; Abdillah, Ahmad Hendrik Said; Arifky, Moh. Rizky Dwi; Septian, Yanuar; Zamzam, Said Agil (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2025)
This community service activity aims to increase the digital promotion capacity of the Ponorogo Pak Ici Chicken Satay MSME through assistance in managing Instagram feeds. The method used is Participatory Action Research (PAR), which places partners as active subjects in all stages of the activity, from problem identification to evaluation. The activity is carried out through initial observation, technical training in taking product photos, writing captions, scheduling content, and direct practice in using Instagram as a promotional tool. The results of the activity show an increase in partners' ability to manage social media content independently, with a more attractive and consistent Instagram feed. Customer interaction has increased, and partners have begun to understand the importance of visual identity and digital strategy in expanding market reach. In conclusion, the PAR approach is effective in encouraging MSME independence in digital promotion and can be used as a model for similar assistance to other MSMEs facing marketing challenges in the technology era.